Manajemen Risiko Dalam Sistem Informasi - Sigit Wijanarko (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
Business is supported with information systems. Business process is expected to run normal and stable, and deliver outputs or service as expected. However in many systems, there are risks. Risks may be either supportive or disruptive. The occurrence of risk may influence the performance of the systems. Risk management is needed during the utilization of information systems. Risk Identification, Risk Assessment and Mitigation Strategy are example of Risk Management factors. Risk Management may varies in line with type of business being supported.